Exploring students’ complaints behaviour for telecommunication industry in Malaysia / Syahmi Harudin, Siti Daleela Mohd Wahid and Nor Khasimah Aliman - Mohd Wahid, Siti Daleela; Aliman, Nor Khasimah; Harudin, Syahmi (Faculty of Business Management, 2013)
The purpose of this study was to ascertain the relationship between students’ complaint behaviour and defection in Malaysian telecommunication industry. Self administered questionnaires were used to collect data. A total of 366 university students from 18 Malaysian public higher learning instituition were recruited to participate in this study. The regression analysis were employed to explore the relationship between the two variables. The study demonstrated that there is a strong positive linear relationship between students’ complaint behavior and defection.The study also found that the influence of private complaint on the defection is much stronger than public complaint which corroborates with the previous study.